2019
DOI: 10.1002/jimd.12152
|View full text |Cite
|
Sign up to set email alerts
|

Ochronotic pigmentation is caused by homogentisic acid and is the key event in alkaptonuria leading to the destructive consequences of the disease—A review

Abstract: Ochronosis is the process in alkaptonuria (AKU) that causes all the debilitating morbidity. The process involves selective deposition of homogentisic acid (HGA)‐derived pigment in tissues altering the properties of these tissues, leading to their failure. Some tissues like cartilage are more easily affected by ochronosis while others such as the liver and brain are unaffected for reasons that are still not understood. In vitro and mouse models of ochronosis have confirmed the dose relationships between HGA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
50
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 52 publications
(61 citation statements)
references
References 87 publications
(145 reference statements)
0
50
0
1
Order By: Relevance
“…Lichtenstein and Kaplan also reported that pigment was barely found in veins, which are under less pressure than the arterial system [7]. Scleral pigmentation within the eye has also been postulated to be due to UV light damage and physical stress arising from ocular muscle contractions [16]. The pattern of pigmentation in both AKU mice and humans suggests that mechanical loading increases the susceptibly of ECM to pigmentation, as observed here in areas of greater compressive load and tensile strain in mice; however, this remains to be established by experimental intervention in mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lichtenstein and Kaplan also reported that pigment was barely found in veins, which are under less pressure than the arterial system [7]. Scleral pigmentation within the eye has also been postulated to be due to UV light damage and physical stress arising from ocular muscle contractions [16]. The pattern of pigmentation in both AKU mice and humans suggests that mechanical loading increases the susceptibly of ECM to pigmentation, as observed here in areas of greater compressive load and tensile strain in mice; however, this remains to be established by experimental intervention in mice.…”
Section: Discussionmentioning
confidence: 99%
“…The structure of ochronotic pigment, and the mechanism of its deposition/formation remains unknown, as recently discussed in a review by Ranganath et al [16]; it is not known whether ochronosis occurs by initial binding of HGA itself, or an oxidised intermediate, or as ochronotic pigment [16]. Ochronotic pigment is deposited in connective tissues, most of which contain collagen as a key component of the ECM.…”
Section: Introductionmentioning
confidence: 99%
“…Data indicate that symptoms with the highest impact for patients were those related to pain and ruptures, disability and inability to perform normal routines, emotional/mental health issues, and heart complications. While the majority of participants rated the impact of visual pigmentation as “not at all” or “not very high,” pigmentation in the eyes and ears reflect burden of pigment throughout the body and is the major pathophysiology in AKU which leads to tissue damage . It is vital that HCPs be informed of these findings to optimize the management and improve the quality of life of these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While the majority of participants rated the impact of visual pigmentation as "not at all" or "not very high," pigmentation in the eyes and ears reflect burden of pigment throughout the body and is the major pathophysiology in AKU which leads to tissue damage. 17 It is vital that HCPs be informed of these findings to optimize the management and improve the quality of life of these patients. Therapeutic alternatives are lacking for the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Although ochronotic pigmentation has been associated with collagen, 26‐28 the mechanism of ochronotic pigmentation is unknown. It is thought that ochronotic pigment could be formed due to the oxidation of HGA to BQA as an intermediate step, although it is not known whether initial binding to collagenous matrix occurs as HGA, the BQA intermediate or as ochronotic pigment itself 29 . A recent study using NMR and EPR spectroscopy suggests that formation of hydroquinones and radicals that causes collagen degradation in AKU cartilage 30 .…”
Section: Discussionmentioning
confidence: 99%